Ayurvedic Management of Deep Vein Thrombosis. - A Case Study - Rathore, Monika; Sharma, Gyan Prakash; Sharma, Mahesh Kumar; Sharma, Renu (International Research Journal of Ayurveda & Yoga, 2022)
The Formation of a Blood Clot [thromb] in the Deep Veins is known as Deep Vein Thrombosis. After ischemic heart disease [IHD] and stroke, deep vein thrombosis is the third most frequent vascular illness, and it is a silent killer. Deep Vein Thrombosis affects about 0.1 percent of the population each year, pain, swelling, redness, warmth and other symptoms are typical. Various western medicine therapy modalities and medications, such as surgical interventions, tissue plasminogen activators, and anti-coagulants for time to break blood clots, all have their own limitations and adverse effects, in addition to being extremely costly nowadays. According to Ayurveda, the aetiology, indications, and symptoms of DVT are identical to those of Raktavrita vata, siragata vata, Gambhira vatarakta, and so on. Acharya Charaka, Sushruta, and Vagbhata all talked on how to treat these ailments. Because they are all Rakta Pradoshja vikara, they just discussed Raktamokshana therapy. However, in the current case study, external application of Ayurvedic lepa combined with bheshaja chikitsa i.e. Raktashodhaka / Raktaprasadhana medicines showed promising results, especially in reducing swelling, redness, itching, and pain without causing any side effects. According to Ayurveda, the present case of DVT with stroke was diagnosed as Ekanga shotha/ Raktavrita vata and pakshaghata. Various Ayurvedic panchakarma methods and internal medications have shown promising outcomes, particularly in minimising edoema [of the left limb caused by DVT] and thrombosis [in the proximal superficial femoral vein and common femoral vein] in deep veins is less severe.